The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.lungcan.2015.05.019
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET maximum standardized uptake value is prognostic for recurrence and survival after stereotactic body radiotherapy for non-small cell lung cancer

Abstract: Objectives Glucose metabolic activity measured by [18F]-fluoro-2-deoxy-glucose positron emission tomography (FDG-PET) has shown prognostic value in multiple malignancies, but results are often confounded by the inclusion of patients with various disease stages and undergoing various therapies. This study was designed to evaluate the prognostic value of tumor FDG uptake quantified by maximum standardized uptake value (SUVmax) in a large group of early-stage non-small cell lung cancer (NSCLC) patients treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 33 publications
1
56
0
Order By: Relevance
“…Pre‐treatment maximum SUV ≥ 4.1 was the lone predictor of PD in our series, based on both multivariate and univariate analysis. Most studies use a maximum SUV > 2.5 as the threshold for malignancy, and prognostic thresholds are 3–3.5 …”
Section: Discussionmentioning
confidence: 99%
“…Pre‐treatment maximum SUV ≥ 4.1 was the lone predictor of PD in our series, based on both multivariate and univariate analysis. Most studies use a maximum SUV > 2.5 as the threshold for malignancy, and prognostic thresholds are 3–3.5 …”
Section: Discussionmentioning
confidence: 99%
“…However, the cut-off was difficult to determine. Several studies suggested that a bed cut-off of approximately 100 is significantly correlated with patient outcome 17,[19][20][21][22]26 ; however, other studies, including the meta-regression by Zhang et al, did not show that association 18,24,25,27,29 .…”
Section: Key Evidencementioning
confidence: 98%
“…Twelve retrospective observational studies investigated the most appropriate bed cut-off in association with patient outcomes [17][18][19][20][21][22][23][24][25][26][27][28] . Again, the studies were considered to be very low quality because of their retrospective design.…”
Section: Key Evidencementioning
confidence: 99%
See 2 more Smart Citations